PAINLESS CARDIAC ISCHEMIA AND RHEUMATOID ARTHRIT - Yarmukhamedova Saodat Khabibovna; Khusainova Munira Alisherovna; Yarmatov Suvon Totlibayevich; Makhmudova Khanuza Davranovna (Journal of new century innovations, 2023)
Rheumatoid arthritis (RA) is an autoimmune rheumatic disease of unknown etiology characterized by chronic erosive arthritis and systemic inflammatory damage to internal organs. In Uzbekistan, RA affects about 1.5% of the entire adult population. RA most often affects people aged 30-50 years. Women get sick 5 times more often than men. The main cause of mortality in RA are cardiovascular catastrophes (myocardial infarction (MI), cerebral stroke (СS) den cardiac death (SCD)). According to a meta-analysis of prospective studies, the risk of cardiovascular mortality in RA is 60% higher than in the general population. Cardiovascular complications (CVD) caused by atherosclerotic vascular lesion in RA have features characterized by multiple coronary vascular lesions; early relapses of acute coronary syndrome; increased mortality after the first MI and a high frequency of "asymptomatic" MI (relative risk (HR) – 2.13).